Abundance, richness and diversity of arbuscular mycorrhizal fungi associated with different grass species in semiarid region - SINGH, HARSH VARDHAN (Indian Phytopathology, 2017)
In arid and semiarid region grasses are most abundantly. Among herbaceous species, grasses play an important role in livestock feeding in the arid and semi-arid region, especially in water-limited conditions. In arid and semi-arid regions, grasses are more dominated in rangelands and highly dependent on mycorrhization. Root and rhizosphere soil of fifteen grass species were collected to study at Jhansi the root colonization and AM fungal spore population structure. The potential of AM fungal root colonization varied between highest 85.5 percent in C. ciliaris to lowest 16 percent in Paspalum notatum. AM fungal spore abundance (2394.1/100 g rhizosphere soil) was observed with grass species C. ciliaris. A total of 9 AM fungal species isolated and identified. Genus Glomus was the most abundant genus in all selected grass species. There is no clear relationship between root colonization potential and AM fungal spore abundance. All the grass species showed higher AM fungal diversity in their rhizosphere soil. It is clear from this study that grass species are dependent on AM fungal association and had species diversity in the natural ecosystem. Diversity and evenness in AM fungi across the grass species rhizosphere had no any significant relation, however, grass species had higher AM fungi species richness showed less evenness.